PENGARUH LIFESTYLE DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE IPHONE MELALUI CITRA MEREK SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA GENERASI Z) - Salafudin Al-Ayubi; Herynd Angga Rizqi; Raully Sijabat (CV. Adiba Aisha Amira, 2024)
This study was made with the aim of knowing and analyzing more deeply the influence of lifestyle and quality on purchasing decisions for iPhone mobile phone products in generation Z through brand image as an intervening variable. The study used quantitative research methods with research data collection through questionnaires distributed online. The population in the study were all generation Z who reside or domiciled in Semarang. Then the sample was determined using non-probability sampling technique with purposive sampling method so that a sample of 30 respondents was obtained. Based on the test results, it shows that lifestyle has no effect on purchasing decisions with a P value of 0.157, product quality affects purchasing decisions with a P value of 0.003, brand image affects purchasing decisions with a P value of 0.581. Then lifetsyle has no effect on brand image with P values of 0.581, product quality affects brand image with P values of 0.000. Furthermore, brand image is able to act as an intervening variable between the effect of product quality on purchasing decisions, but is unable to influence lifestyle on purchasing decisions.